The Evolution of Promising Practices for University Supervisors of Candidates in Yearlong Clinical Experiences - Strieker, Toni Shinn; Langub, Lee; Wright, Marcia (Educational (Re)naissance, 2016)
This paper describes the exploration of a team of university supervisors and faculty who were charged with identifying effective practices for university supervisors who evaluated teacher candidates enrolled in yearlong co-taught clinical experiences. The paper discusses the need for greater collaboration in reflective dialogue among the candidate, the collaborating teacher and the supervisors. In addition, the paper discusses the exploration of GROW, a candidate goal-setting structure, as well as 3-way conversations and video-elicited reflections as promising practices for university supervisors.